(untitled) (Bioagro, 2020)
Cowpea is an important crop for the food security of the world population. However, their production is constantly affected by weed interferences. The objective of this research was to determine the effect of two different weeds at different densities of competition on the growth characteristics of the crop. The study was conducted using a randomized block design in a factorial arrangement of the treatments (2x4 for analysis in cowpea, and 2x3 for weeds). The weed species (Cenchrus echinatus and Rottboellia exaltata) and four competition densities (zero, two, four, and six individuals per pot), with four repetitions, were studied at the crop flowering stage. We measured leaf area, leaf and stem dry mass, root dry mass (RDM), dry mass of the aerial part (DMAP), total dry mass, and the ratio (RDM/DMAP); additionally, the dry mass of the aerial part and root (DMAW and DMRW) of the weeds was measured. The increase in the density of the weeds resulted in a decrease in the values ​​of all the variables of the crop. In the case of weeds, C. echinatus showed higher DMAW than R. exaltata although there were no differences in DMRW. Both weeds negatively affect the growth of bean plants, though with C. echinatus the effect is even greater. The interference effect is higher as the density of the weeds increases.